Armenia : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in the Republic of Armenia during 1995-96. Stabilization and economic growth continued in 1995 and 1996. Official estimates indicate that real GDP increased by 6.9 percent in 1995 and by 4.3 percent during the first six months of 1996 compared with the same period of the preceding year. The trade sector grew by 75 percent in 1995 and 18.5 percent during the first six months of 1996, increasing its share in GDP from 4 percent in 1994 to 9 percent in 1996.